Initial Study of Converting Sound Energy into Electrical Energy - Muhammad Salleh, Hamizah; Yahya, Musli Nizam (Journal of Sustainable Manufacturing in Transportation, 2022)
This study concerns on finding alternative source of energy by finding out the method of converting available and unused sound energy into electrical energy. The purpose of this study includes to investigate the possibility of converting sound wave in a range between 70 dB to 80 dB into electrical energy by determining the effectiveness of the method to transform sound wave into electrical energy and study the percentage error between the theoretical and experimental output voltage produced. An electronic circuit-based experiment was conducted to fulfill the objectives of the study. Sound energy was converted into electrical energy by using microphone transducer, then the brightness of bulb and the voltage reading was observed and tabulated. Theoretical and experimental voltage value were compared and being represented in percentage error value. The data shows that there is potential of converting sound into electricity through the suitable electrical circuit and the output voltage increase linearly with the sound pressure levels (SPL) of the sound sources. Further research should include the study of relationship between distance of sound sources and the transducer, and the output voltage produced